The The Mediating Role Of Trust In The Influence Of Viral Marketing And Online Consumer Reviews On Purchasing Decisions Skintific Product In TikTok - Dewi Murni; Muhartini Salim (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Online shopping in Indonesia will continue to increase along with technological advances, Data collected by APJII and Suara.com shows that "more than 74% of Indonesians choose to shop online." This study aims to examine the mediating role of trust in the influence of viral marketing and online consumer reviews on purchasing decisions through trust. The data obtained by this study through a questionnaire from 100 respondents of Skintific users on TikTok. This research data is processed using SEM (Structural Equation Modeling) using the SmartPLS4 application. The results of this study are Viral Marketing has a significant impact on Trust, Online Consumer Reviews has a significant impact on Trust, Trust has a significant impact on Purchasing Decisions, Viral Marketing has a significant impact on purchasing decisions, Online Consumer Reviews has a significant impact on Purchasing Decisions, Viral Marketing has a significant impact on Purchasing Decisions through Trust, Online Consumer Reviews has a significant impact on Purchasing Decisions through Trust. The implication of this research for the Skintific company is that it is expected to always maintain a good message on Viral Marketing, create a good reputation in consumer perceptions starting from the products sold, the services provided, and other aspects that appear in TikTok media.